Protic ionic liquid attenuates the deleterious actions of urea on alpha-chymotrypsin - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil; Byrne, Nolene (Physical Chemistry Chemical Physics, 2011)
We present a biocompatible ionic liquid, triethyl ammonium acetate (TEAA), that attenuates the denaturation action of a non-ionic chaotrope, urea, on the industrially relevant proteolytic enzyme alpha-chymotrypsin.